Genetic diversity analysis and cytogenetic profiling of Assamese buffaloes from North-East India - Mishra, B P; Prakash, B; Kataria, R S; Sadana, D K; Kathiravan, P; Das, G C; Goswami, R N; Joshi, B K; Bhasin, V; Rasool, T J; Bujarbaruah, K M (The Indian Journal of Animal Sciences, 2011)
In the present study cytogenetic profiling and genetic characterization using microsatellite genotyping was carried out on Assamese swamp buffalo population. Microsatellite data analysis for 23 markers indicated substantial genetic variation existing in the buffalo population. Sufficient allelic diversity was observed with 133 alleles present across different loci. The genetic diversity analysis of Assamese buffaloes displayed moderate to high level of within population variability in terms of mean number of alleles per locus (5.78) and heterozygosity estimates, viz. mean observed (Ho = 0.618) and expected heterozygosity (He = 0.665). The Assamese buffalo population showed low heterozygote deficiency (FIS=0.029). Mean polymorphic information content (PIC) across the 23 loci was 0.611, which indicated suitability of the marker panel for diversity analysis in these buffaloes. Bottleneck analysis indicated no recent genetic bottleneck in the Assamese buffalo population. Further, cytogenetic screening of 46 Assamese buffaloes indicated riverine (2n=50) or hybrid (2n=49) status. None of the animals had a typical pure swamp karyotype (2n=48). Thus, majority of the investigated animals were characterized as riverine type, which is in contrast to the general classification of Assamese buffaloes as swamp type derived from their morphological and behavioral similarity to swamp buffaloes.